Efficient Synthesis of the 6-Deoxy-l-talose-Containing Pentasaccharide Corresponding to the Cell Wall O-Polysaccharide of Escherichia coli O66 - Bag, Puja; Sahaji, Samim; Misra, Anup Kumar (Synthesis, 2024)
The pentasaccharide repeating unit containing 6-deoxy-l-talose corresponding to the cell wall O-polysaccharide of Escherichia coli (E. coli) O66 strain has been successfully synthesized in very good yield using sequential glycosylations of judiciously functionalized monosaccharide intermediates. Incorporation of the β-d-mannosidic linkage and 6-deoxy-α-l-talose in the pentasaccharide was achieved in excellent yield.
Keywords: carbohydrates; glycosylation; glycosides; oligosaccharides; synthesis